"I felt like a lonely person in the desert" : a case study on factors moderating interunit communication in multinational headquarters-subsidiary relationship - Bagdasarov, Riina (2017)
One of the biggest challenges for internationalizing businesses is to develop and maintain efficient internal communication processes across national and cultural borders. This thesis aims to examine what are the most important organizational structures and communicational practices for a successful multinational headquarters-subsidiary relationship, and what do the communicational practices, such as the mechanics of language use and interunit knowledge-transfer, imply about the efficiency of global co-operation. This study considers the experiences of one case company’s Finnish headquarters and Dutch subsidiary on internal communication in a crucial phase of internationalization. The data was collected by interviewing Finnish and Dutch managers and employees working in different positions in the case company. This method enabled an in-depth focus on the perceptions of interunit communication between the globally dispersed units. A qualitative, inductive research method was used in this study to allow the results to naturally emerge from the data while interpreting the phenomenon of interunit communication within a real-life setting of one company. The findings supported the prior research highlighting the multinational company as a knowledge-based network, and brought forth the importance of efficient knowledge-transfer processes as a competitive advantage of multinational companies. Contrary to prior research, the issue of cultural differences was not experienced as a significant risk for either interunit communication nor the headquarters-subsidiary relationship in this case company. However, diversity in languages and communicational practices was seen to hinder the interaction between the units. The results indicated that language and communication management were required specifically in the early phase of internationalization of the case company to be able to build a successful interunit relationship when aiming for both local responsiveness and global integration.